Gasbag phase-change carbon dioxide energy storage: Development and economic study - Ao Ren; Yilin Liu; Qiji Sun (Energy Geoscience)
The Gasbag Phase-change Carbon Dioxide Energy Storage System leverages elastic gasbags to store carbon dioxide under varying geographical conditions. This approach utilizes the phase-change sensible heat effect to efficiently manage energy storage and release. This technology requires lower pressure and temperature control, resulting in reduced energy consumption and improved efficiency. Additionally, it is less restricted by geographical factors to a certain extent, enabling the formation of a closed-loop system. This contributes to the development of new energy utilization systems. The article examines and compares two experimental energy storage projects employing elastic gasbags to maintain a constant pressure supply of carbon dioxide on the low-pressure side. It further details the precise calculation methods for system cycle efficiency and energy storage density while analyzing energy losses incurred during the storage and release phases. Finally, an economic analysis is conducted using specific data, demonstrating that optimizing temperature and pressure parameters at various nodes enhances overall system efficiency while reducing energy consumption. Furthermore, the study highlights the system's high sensitivity to grid electricity prices. This research is anticipated to contribute to the development of more efficient and reliable energy storage solutions for power systems, addressing the growing energy demands and sustainability challenges.